Effect of Placement Method of Crop Residue and Irrigation on Soil Physical Properties and Plant Production - Dwl Putro Tejo Baskoro (Jurnal Ilmu Tanah dan Lingkungan, 2005)
A proper management of crop residue can increase crop production since it plays an important role on increasingwater availability. The effect of crop residue application on soil productivity depends on many factors. In this research. theeffect of placement of crop residue and irrigation on soil physical properties and crop production were examined under field condition on dry season. The result showed that crop residue placement had no significant effect on all parameters of measured soil physical properties both under dry condition (no irrigation) and wet condition (with irrigation). The effects ofcrop residue placements on maize growth were also not significant. Nevertheless there was a tendency that surface application produced higher biomass than buried application. On grain yield, however. the effect of crop residue placement was significant. especially under dry condition with no water applied Surface application of crop residues produced higher grain yield than buried application.